Seasonal changes in stress indicators in high level football - Faude, O.; Kellmann, M.; Ammann, T.; Schnittker, R.; Meyer, T. (International Journal of Sports Medicine, 2011)
This study aimed at describing changes in stress and performance indicators throughout a competitive season in high level football. 15 players (19.5±3.0 years, 181±5 cm, 75.7±9.0 kg) competing under professional circumstances were tested at baseline and 3 times during the season 2008/09 (in-season 1, 2, 3). Testing consisted of the Recovery-Stress Questionnaire for Athletes (Total Stress and Recovery score), vertical jump tests (counter movement and drop jump (DJ)), and a maximal ramp-like running test. Average match exposure was higher during a 3-weeks period prior to in-season 3 compared to in-season 1 and 2 (1.5 vs. 1 h/week, p=0.05). Total Stress score was elevated at in-season 1 and 2 compared to baseline (p<0.01) with a further increase at in-season 3 (p<0.03; generalized eta squared (?2g)=0.37). Total Recovery score was decreased at in-season 1 and 3 compared to baseline (p<0.05; ?2g=0.21). Maximal running velocity (Vmax) and jumping heights were not significantly affected (?2g?0.04). Changes in DJ height and Vmax between baseline and in-season 3 were correlated with the corresponding changes in Total Stress score (r=-0.55 and r=-0.61, p<0.03). Usual match exposure during a professional football season does not induce relevant changes in performance indicators. Accumulated stress and a lack of recovery towards the end of a season might be indicated by psychometric deteriorations.